Experiences Of Motherhood: Challenging Ideals - Frizelle, Kerry; Hayes, Grahame (PINS-Psychology in Society, 2026)
This qualitative study explores how "ideal" images of motherhood have come to interact with the personal everyday experiences of mothers Four mothers participated in individual, semi-structured interviews The data was organised and analysed under thematic headings. Three main themes are highlighted in this study: a mother's account of the maternal ideal, the experience of maternal ambivalence, and motherhood as a natural condition The analysis provides insight into the personal experience of motherhood and highlights its complex and multifaceted nature The study illustrates the oppressive nature of maternal ideals as mothers attempt to achieve the unachievable in their everyday experiences of motherhood. It is argued that tensions coexist within a mother that render her neither as "bad" as society fears nor as "good" as society desires (Parker, 1996). A reconstruction of the "ideal mother'' emerged as the mothers provided a personal account of their experiences of motherhood.